The role of butyrylcholinesterase in the regulation of cognitive dysfunction in minimal hepatic encephalopathy: A potential blood marker of disease evolution - Yang, Xuhong; Dang, Pei; Liu, Wenxiao; Ma, Wanlong; Ge, Xin; Zhu, Kai; Wang, Minglei; Huang, Xueying; Ding, Xiangchun; Wang, Xiaodong (Frontiers in neurology, 2022)
Patients with cirrhosis commonly experience minimal hepatic encephalopathy (MHE), and alterations in neurotransmitters have been thought to be related to cognitive function. However, the relationship between alterations in peripheral and central butyrylcholinesterase (BuChE) with MHE disease progression remains unknown. As such, this study was designed to investigate potential changes in peripheral and central BuChE activity and their effects on cognitive function in the context of MHE.Background and aimsPatients with cirrhosis commonly experience minimal hepatic encephalopathy (MHE), and alterations in neurotransmitters have been thought to be related to cognitive function. However, the relationship between alterations in peripheral and central butyrylcholinesterase (BuChE) with MHE disease progression remains unknown. As such, this study was designed to investigate potential changes in peripheral and central BuChE activity and their effects on cognitive function in the context of MHE.We enrolled 43 patients with cirrhosis secondary to hepatitis B, 20 without MHE and 23 with MHE, and 25 with healthy controls (HC). All the selected subjects underwent resting-state functional MRI, and the original images were processed to obtain the regional homogeneity (ReHo) brain maps. Thereafter, the correlation of BuChE activity with ReHo, number connection test of type A (NCT-A), and digital symbol test (DST) scores with MHE patients were analyzed using Person correlation analysis. Meanwhile, we purchased 12 Sprague-Dawley (SD) rats and divided them into an experimental group (n = 6) and a control group (n = 6). The rats in the experimental group were intraperitoneally injected with thioacetamide (TAA) to prepare MHE model rats. After modeling, we used the Morris water maze (MWM) and elevated plus maze (EPM) to assess the cognition function and exploratory behavior of all rats. The activity of serum, hippocampus, and frontal lobe tissue BuChE was detected by ELISA.Materials and methodsWe enrolled 43 patients with cirrhosis secondary to hepatitis B, 20 without MHE and 23 with MHE, and 25 with healthy controls (HC). All the selected subjects underwent resting-state functional MRI, and the original images were processed to obtain the regional homogeneity (ReHo) brain maps. Thereafter, the correlation of BuChE activity with ReHo, number connection test of type A (NCT-A), and digital symbol test (DST) scores with MHE patients were analyzed using Person correlation analysis. Meanwhile, we purchased 12 Sprague-Dawley (SD) rats and divided them into an experimental group (n = 6) and a control group (n = 6). The rats in the experimental group were intraperitoneally injected with thioacetamide (TAA) to prepare MHE model rats. After modeling, we used the Morris water maze (MWM) and elevated plus maze (EPM) to assess the cognition function and exploratory behavior of all rats. The activity of serum, hippocampus, and frontal lobe tissue BuChE was detected by ELISA.BuChE activity gradually decreased among the HC, patients with cirrhosis, and MHE groups (all P < 0.01). We observed a linear correlation between serum BuChE and NCT-A and DST scores in MHE patients (all P < 0.01). We noted that BuChE activity can negatively correlate with ReHo values in the left middle temporal gyrus and left inferior temporal gyrus, and positively correlate with ReHo values in the right inferior frontal gyrus, and also found that the peripheral BuChE activity of MHE rats was significantly lower than their control counterparts, and the BuChE activity in frontal lobe extracts was significantly higher than the control rats (all P < 0.05).ResultsBuChE activity gradually decreased among the HC, patients with cirrhosis, and MHE groups (all P < 0.01). We observed a linear correlation between serum BuChE and NCT-A and DST scores in MHE patients (all P < 0.01). We noted that BuChE activity can negatively correlate with ReHo values in the left middle temporal gyrus and left inferior temporal gyrus, and positively correlate with ReHo values in the right inferior frontal gyrus, and also found that the peripheral BuChE activity of MHE rats was significantly lower than their control counterparts, and the BuChE activity in frontal lobe extracts was significantly higher than the control rats (all P < 0.05).The altered activity of BuChE may contribute to cognitive impairment in MHE patients, which may be a potential biomarker of disease evolution in the context of MHE.ConclusionThe altered activity of BuChE may contribute to cognitive impairment in MHE patients, which may be a potential biomarker of disease evolution in the context of MHE.